Molecular structural dynamics probed by ultrafast X-ray absorption spectroscopy - Bressler, Christian; Chergui, Majed (Annual review of physical chemistry, 2010)
The ability to visualize molecular structure in the course of a chemical reaction or a biological function has been a dream of scientists for decades. X-ray absorption spectroscopy (XAS) is ideal in this respect because it is chemically selective and can be implemented in any type of medium. Furthermore, using X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) in laser pump/X-ray probe experiments allows the retrieval of not only the local geometric structure of the system under study, but also the underlying electronic structure changes that drive the structural dynamics. We review recent developments in picosecond and femtosecond XAS applied to molecular systems in solution. Examples on ultrafast photoinduced processes such as intramolecular electron transfer, low-to-high spin change, and bond formation are presented.